Faktor Risiko Kejadian Katarak pada Pasien Pria Usia 40-55 Tahun di Rumah Sakit Pertamina Balikpapan - Sari, Andi Dewi; Masriadi, Masriadi; Arman, Arman (Window of Health : Jurnal Kesehatan, 2018)
Cataracts occur due to opacities in the lens of the eye resulting in hanging of light into the eyeball, so the vision becomes blurred and over time can cause blindness. One of the most common causes of blindness worldwide is cataracts. Increased cases of cataract occur in Balikpapan Pertamina Hospital for the last 3 months in January to March that is 142 cases, 173 cases and 188 cases. Cataract events are associated with the causes of diabetes mellitus, economic status, smoking habits, UV exposure, and protein consumption habits. The purpose of this study was to analyze the magnitude of risk factors with the incidence of cataracts in male patients aged 40-55 years in Balikpapan pertamina hospital. The type of research used in this research is analytic observational study with case control study design. The sample in this research consist of case and control by using method of Purposive Sampling, case sample that is male patient age 40-55 cataract treatment and screening at Pertamina Hospital Balikpapan Year 2017. The control sample of this research is male patient age 40-55 which is not suffering from cataract treatment and screening at Pertamina Hospital Balikpapan 2017. The results showed that diabetes mellitus (OR = 4.419; 95% Cl: 1,991-9,809), economic status (OR = 2.852; 95% Cl: 1,346-6,042) Smoking habit (OR = 3,850; 95% Cl: 1,785-8,304), Occupation exposed to UV (OR = 3,217; 95% Cl: 1,523-6,795) is a risk factor for Cataract incidence. While the consumption of protein (OR = 0.110; 95% Cl: 0,046-0,264) is a protective factor incidence of cataracts. Based on multivariate analysis found that the most influential risk factors were diabetes mellitus (p = 0,000) and occupation exposed to UV (p = 0,001) on cataract incidence.